Analisis Perancangan Sistem Informasi Akuntansi Pencatatan Dan Pengelolaan Keuangan Pada Yayasan Panti Asuhan Harapan Karomah - Linda Yunita; Neneng Neneng; Auliya Rahman Isnain; Prita Dellia (Universitas Teknokrat Indonesia, 2022)
Yayasan Panti Asuahan Hrapan Karomah is a social institution or non-profit institution that has the responsibility to provide social welfare services to the children of the residents of the orphanage. Therefore, the manager of the orphanage must be able to manage the orphanage properly, one of which is in terms of financial management. Currently, the Harapan Karamah orphanage is in the process of recording both revenues and expenses using a manual system. A manual system causes many errors of risks. Therefore, to minimize the risks that exist and also facilitate the financial management of the orphanage, a computerized information system is needed. In addition, it can also make it easier for the manager of the orphanage and also donors to monitor and evaluate the orphanage's finances which can be accessed quickly and at any time. This study aims to create a website-based financial administration information system. The software development method used is the Waterfall method which includes requirements analysis, system design, implementation, testing, and system maintenance. The development of this system uses the PHP programming language, MySQL database, and the CodeIgniter framework. The result of this research is an information system that can be used to process data and financial data reports. Based on the test results, the system being developed can run according to its function.